Meningkatkan Kedisiplinan dan Keterampilan Berbahasa yang Baik melalui Bimbingan dari Guru BK di MTsN 1 Batang Hari - Nabila Dwi Septia Fiveronika (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2022)
Students disipline and responsibility in carrying out learning is still very lacking. At this time generally the problem is still with delays when going to school, irresponsible for the tasks that have been given by teachers,many students have difficulty understanding lessons when the teaching and learning process is in progress,and there are students who cannot control their emotiuns which is in self.Good language skills are very influential for these students, many students think that Indonesian does not need to be studied, the reason is that all Indonesians can speak Indonesian, most of the students use Indonesian in a foreign language or slang and by using In this slang, students arbitrarily speak and behave with anyone, especially to the teacher, there are still many students who think that the teacher is like a peer who in the end speaks and behaves impolitely and is not good to hear. The results of this are directed to guadance and counseling teachers at Madrasah Tsanawiyah One Batang Hari, guidance and counseling teachers not only guide students who have problems but guidence and counseling teachers at the school there are organizations that later guidance and counseling teachers evaluate talent interests container on their student. Guidnace and counseling teachers evaluate talent ini interests countained in their students. Guidance and counseling planning at Madrasah Tsanawiyah one Batang Hari continued to be carrin out by guiding the students and providing encouragment and motivation to student to become good students and achivers.The obstacles of guidance and counseling teachers on crrying out plants to improve students dicipline and responsibility that are atructured in the learning process,school that make guidance and counseling teachers a scourage (the teacher who is most feared by all students). Guidance and counseling teachers have not been to control their students by understanding the characteristics of very many students and there are still many students who violate the rules that have been set by the school.The efforts Made by guidance and counseling teachers to overcome the obstacles of student in crrying out dicipline and responsibility,namely by socialisi g the existance of guidnace and counseling in school, getting closed to their students by visiting students homes and looking for student data in order to understand the character prossessed by these student,besides that the guidance and counseling teachers conducts a search for student telent interests in order to find out what talents are prossessed by students at Madrasah Tsanawiyah One Batang hari, by knowing the talents of students, guidance and counseling teachers can develop their identity.the students themselves. Keyword: The;role;of;guidance;and;counseling;teachers;good;discipline;and;language;skills.